High throughput implementation of the new Secure Hash Algorithm through partial unrolling - Michail, Harris; Goutis, Costas E.; Aisopos, Konstantinos; Kakarountas, Athanasios P. (My University, 2005)
A design approach to create small-sized high-speed implementation of the new version of Secure Hash Algorithm is proposed. The resulted design can be easily embedded to operate in HMAC IP cores, providing a high degree of security. The proposed implementation does not introduce significant area penalty, compared to other competitive designs. However the achieved throughput presents an increase compared to commercially available IP cores that range from 43%-1830%. © 2005 IEEE.
Keywords: Hash functions; Field programmable gate arrays (FPGA); Cryptographic hash